Chrysosporium christchurchicum: A new species from India - R.K.S. KUSHWAHA, NEETU TRIPATHI and (Indian Phytopathology, 2005)
Chrysosporium christchurchicum sp. nov., a keratinophilic hyphomycete isolated from soil of India by using cow horn as bait, is described. It has several characteristics which differentiate it from the known species of the genus and is thus described as new.